SOCIAL NETWORKS AS A TOOL FOR IMPLEMENTATION OF SOCIAL-PSYCHOLOGICAL MECHANISMS OF ORGANIZATIONAL CULTURE - V. Voronin; M. Iontseva (Вестник университета)
The article examines the possibilities of using virtual social networks for the implementation of socio-psychological mechanisms for the construction and development of organizational culture. The authors describe social networks as a special virtualized social environment, characterize and describe the features of interaction within it. In the work, much attention is paid to socio-psychological mechanisms - scoring, patricipation, the technology of the expanding core and cascade technology, as well as the organizational conditions for employee motivation.